Epidermal electrodes with enhanced breathability and high sensing performance. (March 2020) - Wang, Y.; Hong, T.; Wang, L.; Li, G.; Bai, N.; Li, C.; Lu, P.; Cai, M.; Wu, Z.; Lu, N.; Yu, B.; Zhang, J.; et al.
Abstract: High breathability of epidermal electronics plays a critical role in long-term attachment and non-irritating contact to the skin. However, most existing skin-mounted electronics use a water-proof substrate ( e.g., 3M Tegaderm), which hinders skin sweating, resulting in interfacial delamination and skin irritation. Here, we report that hydrophilically treated Au nanomeshes (AuNMs) exhibit a sweat evaporation rate significantly faster than that of naked skin while maintaining high stretchability and exceptional conformability. The epidermal AuNM is able to stably sense body motions and detect the strain level of the skin as well as joint bending directions. The sensing capability results from local rupture and fast cold welding of Au nanowires during deformation, which contributes to fast healing or repair of damaged AuNM epidermal circuits. Such substrate-free AuNMs with improved breathability are promising for high performance on skin electronics and beyond. Graphical abstract: Image 1 Highlights: The substrate-free Au nanomeshes can work as epidermal electrodes. The mesh structure contributes to high flexibility and high gas permeability. The hydrophilically treated Au nanomeshes boost the sweat evaporation rate. The Au nanomesh can be used in epidermal signal collection and thermotherapy.